2021
DOI: 10.1002/jia2.25768
|View full text |Cite
|
Sign up to set email alerts
|

Choosing event‐driven and daily HIV pre‐exposure prophylaxis – data from two European PrEP demonstration projects among men who have sex with men

Abstract: Introduction Daily and event‐driven PrEP are both efficacious in reducing the risk for HIV infection. However, the practice of event‐driven PrEP (edPrEP) is less well studied, in particular when provided as an alternative to daily PrEP. We studied regimen preferences and switches, and sexually transmitted infection (STI) incidence. Methods We analysed pooled data from two prospective cohort studies among MSM: Be‐PrEP‐ared, Belgium and AMPrEP, the Netherlands. In both pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
(61 reference statements)
6
12
0
Order By: Relevance
“…Nevertheless, switches between PrEP regimens and (temporarily) interruptions in follow-up and PrEP use occurred. This is consistent with results from other studies, where 17-30% of the PrEP users switched at least once during the study period and 13-69% temporarily interrupted the use of PrEP [18][19][20]. To further enhance preventioneffective PrEP adherence, healthcare providers could offer PrEP as a dynamic intervention over time, such as allowing for switching between PrEP regimens and temporarily interrupting PrEP intake.…”
Section: Dynamics Of Follow-upsupporting
confidence: 89%
“…Nevertheless, switches between PrEP regimens and (temporarily) interruptions in follow-up and PrEP use occurred. This is consistent with results from other studies, where 17-30% of the PrEP users switched at least once during the study period and 13-69% temporarily interrupted the use of PrEP [18][19][20]. To further enhance preventioneffective PrEP adherence, healthcare providers could offer PrEP as a dynamic intervention over time, such as allowing for switching between PrEP regimens and temporarily interrupting PrEP intake.…”
Section: Dynamics Of Follow-upsupporting
confidence: 89%
“…Australia's specific context may in part explain why more participants preferred daily PrEP and why only 14 had switched to non-daily PrEP. However, these findings nonetheless reflect previous research that has also found PrEP users mainly prefer daily PrEP (albeit in contexts where it is considered the gold-standard) (Broady et al, 2021;Coyer et al, 2020;Hoornenborg et al, 2019;Jongen et al, 2021;Reyniers et al, 2018;Vuylsteke et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Globally, most (typically about three-quarters) of those on PrEP take and prefer daily PrEP (Broady et al, 2021;Coyer et al, 2020;Hoornenborg et al, 2019;Jongen et al, 2021;Reyniers et al, 2018;Vuylsteke et al, 2019). However, some PrEP users, when given the choice at study enrolment, chose event-driven PrEP over daily PrEP (Wu et al, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One small European study of 2 PrEP demonstration projects showed similar incidence rates of syphilis between MSM who used on-demand PrEP and those using daily PrEP, whereas a lower incidence of chlamydia and gonorrhea was found among on-demand PrEP users. 39 It will be important to evaluate the incidence of STIs among individuals using on-demand PrEP in comparison with those using PrEP daily in future large epidemiologic studies among patients in routine PrEP care. Fourth, because information on sexual behavior is not routinely collected in primary care, we could not identify a representative concurrent comparison cohort of MSM.…”
Section: Limitationsmentioning
confidence: 99%